Inventarisasi Jenis-Jenis Burung di Kawasan Ekowisata Sungai Gemuruh Teluk Mandeh - Fajar Prima Leonan (RC-INSTITUT, 2023)
Birds play an important role and are animals associated with mangrove forest ecosystems. This study aims to identify bird species in the Sungai Gemuruh Teluk Mandeh ecotourism area from November 2022 to December 2022 using Visual Encounter Survey (VES) and point counting methods. Observations were made in the morning (06:00 – 09:00 WIB) and afternoon (16:00 – 18:00 WIB). Data from studies are analyzed descriptively and presented in the form of tables and figures As a result, there were 18 species of birds in his 10 families, 3 of which were waterfowl. The bird species most frequently found during observations were Passer montanus (Erasia sparrow) and Pycnonotus goiavier (Merbah Cerukcuk).